Conflict Management in a Computer-Supported Meeting Environment - Poole, Marshall Scott; Holmes, Michael; Desanctis, Gerardine (Management Science, 1991)
Computer systems to support decision-making, planning, and negotiation in groups have the potential for wide-ranging application. However, knowledge of their effects is sparse, particularly for difficult situations such as group conflict. This study reports a laboratory experiment to examine how a general purpose group decision support system (GDSS) influenced conflict management in small groups making a budget allocation decision. The study tests a model that posits that GDSS impacts on conflict outcomes are mediated by group interaction processes, particularly how the GDSS enters into group interaction. The model posits seven potential impacts—some positive and some negative—that GDSS technology might have on conflict interaction processes. The impacts do not automatically occur, but depend on the nature of the GDSS and how the group applies it. Hence, a given GDSS might result only in a subset of the seven impacts. Among other things, the model predicts that the particular combination of GDSS impacts that materializes differs across groups and that the balance of these impacts, positive or negative, determines positive or negative conflict outcomes. Groups using a particular GDSS, the Software Aided Meeting Management (SAMM) system, were compared to groups using a manual version of the same decision structures built into SAMM and to unsupported groups. Results indicated that there were differences in the level of conflict in SAMM-supported versus manually-supported and unsupported groups, and in conflict management behaviors adopted by the different conditions. Moreover, there were differences in the impacts of SAMM for different groups, and there is some evidence that these contributed to consensus change. Overall, the theoretical model was supported by the study. This model and approach used in this study seem useful for designing future studies concerning the impacts of computer technology on group judgment and choice.